Prediction of colorectal cancer diagnosis based on circulating plasma proteins - Silvia Surinova; Meena Choi; Sha Tao; Peter J Schüffler; Ching‐Yun Chang; Timothy Clough; Kamil Vysloužil; Marta Khoylou; Josef Srovnal; Yansheng Liu; Mariette Matondo; Ruth Hüttenhain; et al. (EMBO Molecular Medicine)
Abstract Non‐invasive detection of colorectal cancer with blood‐based markers is a critical clinical need. Here we describe a phased mass spectrometry‐based approach for the discovery, screening, and validation of circulating protein biomarkers with diagnostic value. Initially, we profiled human primary tumor tissue epithelia and characterized about 300 secreted and cell surface candidate glycoproteins. These candidates were then screened in patient systemic circulation to identify detectable candidates in blood plasma. An 88‐plex targeting method was established to systematically monitor these proteins in two large and independent cohorts of plasma samples, which generated quantitative clinical datasets at an unprecedented scale. The data were deployed to develop and evaluate a five‐protein biomarker signature for colorectal cancer detection.